(untitled) (Journal of Libya for geographical studies, 2026)
Libya is considered one of the world’s most water-scarce countries due to the limited amounts of rainfall it receives, a condition largely attributed to its astronomical and geographical location. More than 80% of Libya’s territory consists of arid desert lands, and the country lacks permanent surface water resources. Consequently, Libya relies almost entirely on groundwater resources, including both non-renewable aquifers and others characterized by very limited recharge rates. Non-conventional water resources—such as seawater desalination and treated wastewater—contribute only a very small share, not exceeding 2% of the total available and exploited water resources. The continuous growth of the population has led to an increasing demand for freshwater to meet domestic and urban needs, in addition to supporting various economic activities. Approximately 65% of Libya’s population resides in northern coastal cities along the Mediterranean Sea, where most economic activities are concentrated. However, these cities overlie aquifers with limited water reserves and weak recharge potential. Excessive pressure on these aquifers has resulted in groundwater depletion and deterioration of water quality. This situation necessitated the exploitation of non-renewable groundwater resources in the southern region through the Great Man-Made River Project and their transfer to northern cities suffering from water scarcity and high population concentration. As a result, Libya faces numerous challenges in achieving water security, including the vast territorial area of the country, the dominance of arid and semi-arid climatic conditions, the non-renewability of water resources, population concentration in water-scarce regions, the limited contribution of non-conventional water resources, and the very high proportion of water consumption by the agricultural sector.